Kir6.2 E23K polymorphism is related to secondary failure of sulfonylureas in non‐obese patients with type 2 diabetes. Issue 5 (11th April 2013) - Shimajiri, Yoshinori; Yamana, Akiko; Morita, Shuhei; Furuta, Hiroto; Furuta, Machi; Sanke, Tokio
Abstract: Aims/Introduction: The Kir6.2 E23K polymorphism was studied with a special reference to secondary sulfonylurea (SU) failure in non‐obese patients with type 2 diabetes. Materials and Methods: We recruited 278 non‐obese (body mass index ≤30.0 kg/m 2 ) Japanese patients with type 2 diabetes who had a history of SU treatment (for 11.2 ± 6.3 years) and compared the frequency of the secondary SU failure among the genotypes of the polymorphism. Genotyping of the Kir6.2 E23K was carried out by polymerase chain reaction‐restriction fragment length polymorphism. Results: The genotype frequencies of the polymorphism were similar to those previously reported in Japanese patients with type 2 diabetes. The frequency with which patients deteriorated into secondary SU failure was significantly higher in those with the KK genotype than those with EE or EK genotypes. Among 214 patients who eventually received insulin therapy because of secondary SU failure, the period of SU treatment in those with the KK genotype was significantly shorter than those with the EE or EK genotype, although the period from diagnosis to the start of SU treatment was not significantly different. Conclusions: These data suggest that the Kir6.2 E23K polymorphism is related to the acceleration of secondary SU failure in non‐obese Japanese patients with type 2 diabetes.